EMPOWERMENT OF JAMBIâ€™S SONGKET BUSINESSES THROUGH PRODUCT DIVERSIFICATION - Margarettha; Nela Safelia; Hasriati Nasution (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Jambi is a part of Malay history and customs, therefore Songket fabrics become a common viewduring wedding or royal events. Over time, Songket cloth has become part of the social life used byall strata of the society. This condition makes Songket initiated the establishment of a group ofsmall and medium enterprises (SMEs) in Jambi, dedicated for Songket manufacturing and selling.The effort to develop local culture as a national asset is a duty for all Indonesian people, includingJambi University through the â€œDarma of Dedication to the communityâ€. Community serviceprogram initiated by the Ministry of Research, Technology and Higher Education through thescheme of Export Product Development Program (PPPE) aims at conducting guidance andassistance for Jambiâ€™s Songket SMEs through product diversification in order to increase thebusiness of SMEs. The methods of assistance used for SMEs include lectures, discussions,training, demonstrations, mentoring and program evaluation. Lectures, discussions, demonstrationsand training were conducted to increase the knowledge about diversification of products madefrom Songket. Further assistance was done for all the discussions that had been given. To measurethe success of the program, the team would conduct an evaluation from the beginning until the endof the program. The assistance provided by the PPPE of University of Jambi to SME partners ofJambiâ€™s Songket business was able to produce wallets, ladies handbags, tracks, clothes, seatcushions, frames and sandals. The strategy of product diversification is able to increase therevenue for the SME involved.